IMPLEMENTASI MODEL PBL DENGAN PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X-H SMA NEGERI 1 NGLAMES PADA MATERI FUNGSI KUADRAT - Septiyani, Della Angge; Tri Andari; Esthiningtyas S. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve student learning outcomes by applying the Problem Based Learning (PBL) learning model and the Teaching at the Right Level (TaRL) approach. This research is a type of classroom action research that follows stages starting from planning, implementation, observation and reflection. The data obtained was analyzed by calculating the average class score obtained by students and the percentage of students completion. Based on the initial test results, it shows that the mathematics learning outcomes for class XH are still relatively low. Therefore, researchers collaborated with mathematics teachers to improve the learning outcomes of class XH students. The efforts made are by applying the PBL learning model and theTaRL approach to quadratic function material. Based on the results of data analysis, student learning outcomes have increased significantly.The percentage of student completion in the pre-cycle was 3,1%. Meanwhile on the first and second cycles experienced an increase, namely to 60% in the first cycle and 94% in the second cycle.